“Confessional spaces and criminality”: Incest in Alice Walker and Yvonne Vera’s works (Journal for Studies in Humanities and Social Sciences, 2015)
The paper explores incest in Alice Walker and Yvonne Vera’s works as site for contestation of larger forces in society. The portrayal of incest comes at a time where certain “truisms” known to be in Black men in the stereotypification lore are overly dramatised and this tend to submerge genuine and well meaning struggles for racial emancipation and self determination to the periphery. That black men are portrayed as people with unrestricted libido is neither fortuitous nor an incidental project in the aforementioned writers’ works, rather, as a matter of priority it is often easy to take the lesser path by further complicating and bashing the generic punch bag of the Caucasian world. Thus, l argue that the said incestuous relationships are meant to vulgarise in a parallel form the ongoing struggles in America and in Colonial Zimbabwe respectively in the manner of Thomas Rice’s staged minstrels in Antebellum America. The emphasis by Walker and Vera is on the defective forms of lifestyles by people who declare alibis from the struggles and many critics have tended to applaud such projections as characterising a quest for inclusivity of the formerly muffled voices. This article contextualises the crime of incest, in its socio-political realm and refutes the overblown criminality of the black men as a political invention. Cases of incest abound in society and may persist in the unforeseeable future but these are not a preserve of black men.